(untitled) (London Journal of Research In Science: Natural and Formal, 2024)
Following Theodor Kaluza, Itzhak Bars and David Bohms idea, recognizing the rationality of B. Fengs new physics theory, based on five-dimensional space, the corresponding coordinate connotation has determined through reasoning, represent as form as (x, y, z, ict, iat 2 ). Where, a is the curvature acceleration of light, and equals to 10 31 m/s 2 . It is believed to be the limit acceleration in universe, nothing could beyond.